Measuring patient-reported physical functioning and fatigue in myelodysplastic syndromes using a modular approach based on EORTC QLQ-C30 - Antoine Regnault; Farrah Pompilus; Anna Ciesluk; Flora Mazerolle; Rafael Bejar; Robert J. Fram; Douglas V. Faller; Patrick Marquis; Jill A. Bell (SpringerOpen, 2021)
Abstract Purpose Physical functioning and fatigue are key patient concerns in myelodysplastic syndromes (MDS), chronic myelomonocytic leukemia (CMML), and acute myeloid leukemia (AML). The objective of this research was to generate supportive quantitative evidence for modular physical functioning and fatigue measures based on the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire Core 30 items (QLQ-C30) and a customized selection of 10 supplemental items from the EORTC Item Library. Methods The 40 items were completed online cross-sectionally by 51 patients (higher risk [HR] MDS: 53%; CMML: 26%; AML: 10%). Psychometric analyses based on Rasch measurement theory (RMT) were conducted on the QLQ-C30 physical functioning and fatigue domains as well as measures combining QLQ-C30 and supplemental items. A measure of anemia-related symptoms composed of QLQ-C30 and supplemental items covering fatigue, dyspnea, and dizziness was also investigated. Results The QLQ-C30 physical functioning and fatigue domains showed good targeting to the sample and adequate reliability, with few conceptual gaps identified. Combining the QLQ-C30 and supplemental physical functioning and fatigue items improved the conceptual coverage and the reliability of the measures. The patient-reported anemia-related symptom measure showed good measurement performance, underpinned by a clinically meaningful characterization of severity of these symptoms over a spectrum, starting with fatigue, then dyspnea, and finally dizziness (most severe). Conclusion The modular measurement approach of combining EORTC QLQ-C30 and Item Library offers a promising pragmatic solution to the measurement of physical functioning and fatigue, as well as anemia-related symptoms in clinical trials conducted in HR MDS, CMML, and AML.